SHORT TERM ICU MORTALITY AND PATIENTS’S CHARACTERISTICS: A RETROSPECTIVE STUDY IN A COLLEGE HOSPITAL: Pharmaceutical Science-Medicine - SULTAN, INTESSAR; A. ALGHAMD, FERAS; F. ALTHUBITY, ABDULAZIZ; H. ALGHAMDI, WAEEL; A. MAHMOUD, D BASAM (International Journal of Life Science and Pharma Research, 2019)
Intensive care unit (ICU) patients are extremely ill, need frequent monitoring and support, and has the highest reported hospital mortality rates. The aim of the study was to evaluate the characteristics of ICU patients and their short-term mortality. This retrospective study was performed in 2018 at IbnSina National College Hospital in Jeddah, Saudi Arabia. Records of 74 ICU patients hospitalized from January to August 2018 were reviewed for demography, clinical and laboratory data, mechanical ventilation (MV), use of vasopressor, length of stay, and short-term mortality. Sequential Organ Failure Assessment (SOFA) score was calculated. Results showed that most ICU patients were nonelderly (85.1%) men (79.7%) with diabetes (50.7%) and hypertension (44%). The main causes of admission were DKA (21.6%) and neurological (21.6%) emergencies. Only 10.8% received vasopressors but no MV. Short term mortality was 12.2% including only men with significantly high odds ratio in patients older than 40 (p=0.04), cardiac (p=0.008) or hepatic diseases (p=0.003), high SOFA score (>8) (p=0.008), and duration of admission >2 days (p=0.034). In conclusion, our mortality rate was within the lower limit of the globally reported rate of 6-40%; probably because of non-elderly age, associated comorbidities, frequent admission of DKA, infrequent need for vasopressor, and absent need for MV. Mortality was related to old age, underlying cardiac or hepatic diseases, long stay in ICU, and high Sofa score